Clinical efficacy of adjuvant chemotherapy in the treatment of pT4 stage II colorectal cancer with defective mismatch repair status: A protocol for systematic review and meta-analysis. Issue 26 (26th June 2020) - Huang, Li-Bin; Yang, Ting-Han; Yang, Lie; Yu, Yong-Yang; Wang, Zi-Qiang; Wang, Cun; Zhou, Zong-Guang
Abstract: Background: The aim of this systematic review and meta-analysis is to assess the efficacy of adjuvant chemotherapy in patients with stage IIB/C CRC and defective mismatch repair (dMMr) status, and to evaluate what is the determinant risk factor for adjuvant chemotherapy in those patients. Method: A systematic search of PubMed, EMBASE, Web of science, Cochrane Library databases will be performed. All RCTs published in electronic databases from inception to March 19, 2020, with language restricted in English will be included in this review study. Two reviewers will independently perform the Study selection, data extraction, quality assessment, and assessment of risk bias and will be supervised by third party. Outcomes consisted of overall survival, progression-free survival and sufficient information to extract hazard ratios and their 95% confidence intervals and it will be calculated to present the prognostic role of adjuvant chemotherapy in patients with stage IIB/C CRC and dMMR status using Review Manager version 5.3 when there is sufficient available data. Results: The results of this systematic review and meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This study will summarize up-to-date evidence to assess the efficacy of adjuvant chemotherapy in patients with stage IIB/C CRC and dMMR status and provide a scientific and practical suggestions for treatment decision-making. Registration: This protocol has been registered on the International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY) with a registration number of INPLASY202050019.